IMPLEMENTASI IoT DAN SENSOR MULTIFUNGSI DALAM PRAKTIKUM INDUKSI ELEKTROMAGNETIK - Nainggolan, Juliper; Marbun, Juliaster; Surbakti, Mariana; Pardede, Juven (Charm Sains: Jurnal Pendidikan Fisika, 2025)
This study aims to implement an Internet of Things (IoT) and multifunctional sensor system in the electromagnetic induction practicum to enhance students’ conceptual understanding and analytical skills. The research employed a quasi-experimental design with pre-test and post-test models involving 26 students enrolled in the Physics Laboratory Design and Production course. The practicum utilized real-time data acquisition, allowing students to directly observe relationships among magnetic flux variations, induced electromotive force (EMF), and current direction through a digital interface. Results revealed a significant increase in students’ conceptual understanding, with mean scores rising from 59.8% to 81.6% (p < 0.001). Moreover, 84.7% of participants achieved Good to Very Good understanding levels. Questionnaire data indicated high levels of motivation and satisfaction with the IoT integration, particularly regarding interactivity, rapid data analysis, and real-time visualization of physical phenomena. The implementation of IoT and multifunction sensors effectively improved the quality of physics laboratory learning, strengthened analytical thinking skills, and fostered contextual, technology-oriented learning experiences relevant to modern scientific education.